The Development of Sembilan Belas Tahun Song To Prevent Early Marriage In Adolescents - Dariyo, Agoes; Tumanggor, Raja Oloan; Andrianputra, Ezra (Universitas Negeri Surabaya, 2024)
A creative way to implement Law number 16 of 2019 is through developing the song Nineteen Years to prevent early marriage. This qualitative-descriptive research data was collected using a music quality questionnaire and an early marriage prevention questionnaire. The research respondents were 73 teenagers (17-21 years). Data analysis using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) approach. The research results show that the process of creating the song Nineteen Years goes through ADDIE stages which fulfill the dimensions of musical quality (such as poetry, tempo, rhythm, melody, beat, instrument). The song lyrics are relatively simple, easy to understand and memorize. The tempo of the music is classified as medium (moderate). The rhythm of the music is regular and harmonious. Melody implies a message, idea or notion from the songwriter. Beat the music with the beat of the notes, and the right accent. The musical instruments are sufficient to support the song accompaniment. However, video viewing still has shortcomings and needs improvement to improve the quality of video viewing. It is recommended that the government adopt a policy of grounding marriage laws through creative songs so that teenagers can prevent early marriage.